Synthesis of Carbamoylacetates from α-Iodoacetate, CO, and Amines under Pd/Light Combined Conditions - Sumino, Shuhei; Fusano, Akira; Fukuyama, Takahide; Ryu, Ilhyong (Synlett, 2012)
We developed a novel synthetic method of carbamoylacetates from α-iodoacetate, carbon monoxide, and amines under photoirradiation conditions in the presence of a Pd catalyst. This reaction likely proceeds via interplay of radical and organopalladium species.
Keywords: radical reaction; carbonylation; carbamoylacetates; palladium; photo reaction